Parthenolide promotes expansion of Nestin+ progenitor cells via Shh modulation and contributes to post-injury cerebellar replenishment - Jinling, Dong; Liyuan, Feng; Wenying, Fu; Yuting, Huang; Xiangyu, Tang; Xiuning, Huang; Yu, Tang; Qianliang, Ming; Linming, Guo; Ning, Gao; Peng, Li (Frontiers in Pharmacology, 2022)
Background: Regeneration of injuries occurring in the central nervous system is extremely difficult. Studies have shown that the developing cerebellum can be repopulated by a group of Nestin-expressing progenitors (NEPs) after irradiation injury, suggesting that that modulating the mobilization of NEPs is beneficial to promoting nerve regeneration. To date, however, effect of exogenous pharmaceutical agonist on NEPs mobilization remains unknown. Parthenolide (PTL), a sesquiterpene lactone isolated from shoots of feverfew. Although it has been shown to possess several pharmacological activities and is considered to have potential therapeutic effects on the regeneration of peripheral nerve injury, its efficacy in promoting central nervous system (CNS) regeneration is unclear. In this study, we aimed to elucidate the role and possible mechanism of PTL on regeneration in injured CNS after irradiation using a developing cerebellum model. Methods: We investigated the radioprotective effects of PTL on the developing cerebellum by immunoblotting as well as immunofluorescence staining and ROS detection in vivo and in vitro experiments, and then determined the effects of PTL on NEPs in Nestin CFP and Nestin GFP fluorescent mice. Inducible lineage tracing analysis was used in Nestin-CreERT2×ROSA26-LSL YFP mice to label and track the fate of NEPs in the cerebellum after irradiation. Combined with cell biology and molecular biology techniques to determine changes in various cellular components in the cerebellum and possible mechanisms of PTL on NEPs mobilization in the injured developing cerebellum. Results: We found that PTL could attenuate radiation-induced acute injury of granule neuron progenitors (GNPs) in irradiated cerebellar external granule layer (EGL) by alleviating apoptosis through regulation of the cells’ redox state. Moreover, PTL increased cerebellar Shh production and secretion by inhibiting the PI3K/AKT pathway, thus promoting expansion of NEPs, which is the compensatory replenishment of granule neurons after radiation damage. Conclusions: Collectively, our results indicate that activation and expansion of NEPs are critical for regeneration of the injured cerebellum, and that PTL is a promising drug candidate to influence this process.